SPATIAL-TEMPORAL DISTRIBUTION OF NARROW-BARRED SPANISH MACKEREL (Scomberomorus commerson) FISHING GROUNDS IN RIAU ARCHIPELAGO WATERS, INDONESIA - Fardilah, Muhammad Fajar Fajri; Simbolon, Domu; Sondita, Muhammad Fedi Alfiadi; Sari, Tengku Ersti Yulika; Setiawan, Heri (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2024)
Narrow-barred Spanish mackerel (Scomberomorus commerson) is an exportable fish captured by gillnet fishing fleets from Bintan Regency. The fleets are operated in the Riau Archipelago waters but information on their activities is limited. Such information is important to the institution the Agency for Marine and Fisheries Affairs of Archipelagic Riau Province for ensuring the sustainability of the fisheries from both economic and biological perspectives. This study aims to determine the spatial-temporal distributions of the mackerel fishing grounds along the year with reference to the capture data, sea surface temperatures, chlorophyll-a concentrations, and salinities in the last 4 months of 2022. This study analyzed data from a fish export company, the PSDKP office at Tanjungpinang, Bintan, interviews of fishers affiliated with 44 fishing boat samples, and satellite-based marine data. Analysis on the monthly fishing productivity and optimum marine conditions for the mackerels were carried out to determine prospects of five recognized fishing grounds. Besides Lingga Islands, the fishing grounds are highly prospective from August to November. The longest fishing seasons are expected around Bangka Island (11 months). The spatial and temporal patterns show that the north-south-north shifts in fishing grounds that are associated with regional climates, i.e., monsoon winds.